Simulation Analysis and Experiment Research of Transformer Vibration Based on Electric–Magnetic–Mechanic Coupling - Long He; Yongming Zhu; Gang Liu; Chen Cao (Energies)
To research a transformer’s vibration characteristics, a simulation and an experiment are conducted on a 10 kV transformer. The theoretical model for core and winding vibration is established. The electric–magnetic–mechanic multi-physical field coupling model for the transformer core and winding is constructed, yielding voltage and current waveform and magnetic field distributions. The simulation results show that the amplitude of the main flux for core is 1.79 T, the amplitude of vibration acceleration for core is 0.005 m/s2, the magnetic flux leakage is 0.31 T, the amplitude of the vibration acceleration on the side of the winding is 0.0795 m/s2, and the amplitude of vibration acceleration on the front midpoint of winding is 0.0387 m/s2. The transformer vibration experimental platform is constructed, and no-load and load tests are conducted. Empirical findings demonstrate that the acceleration of core vibration is 0.0047 m/s2, and the simulation deviation is 6.38%. The maximum winding vibration acceleration at the side midpoint of phase A is 0.0714 m/s2, and at the front midpoint of Phase B is 0.0416 m/s2. Compared with experiment results, the simulation deviations are 2.1% and 3.3%, respectively. These conclusions indicate an alignment between the experiment and simulation results, thereby confirming reliability of the methodology.